Pengaruh Free Cash Flow, ESG Disclosure dan Tax Planning terhadap Nilai Perusahaan dengan Komite Audit sebagai Pemoderasi - Riris Rotua Sitorus; Priska Yanti Lombu; Sihar Tambun (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to analyze the effect of Free Cash Flow, ESG Disclosure, and Tax Planning on company value, as well as the role of the audit committee as a moderator in this relationship. The type of research conducted is causal research. Causal research aims to test hypotheses about the influence of one or more independent variables on other dependent variables. Based on data obtained from the Indonesia Stock Exchange (IDX) through www.idx.co.id, it is known that the population in this study consists of companies in the energy sector. This study has a total of 102 data points, consisting of 34 company samples from 2022 to 2024. The hypothesis test results prove that Free Cash Flow has a significant impact on Company Value. ESG Disclosure does not have a significant impact on Company Value. Tax Planning does not have a significant impact on Company Value. The Audit Committee moderates the influence of Free Cash Flow on Company Value. The Audit Committee does not moderate the influence of ESG Disclosure on Company Value. The Audit Committee does not moderate the effect of Tax Planning on Firm Value. These findings imply that companies need to manage Free Cash Flow efficiently to enhance firm value, implement ESG Disclosure strategically to deliver tangible benefits, and conduct Tax Planning cautiously. Strengthening the role and independence of the Audit Committee is also crucial to ensuring good corporate governance and supporting the achievement of optimal firm value